A comparison of tutor profiles and observation grades within the Workers’ Educational Association (WEA) 2005 - 2008 - Coward, Philip J. (2013)
The introduction of the 2007 Further Education Teachers’ Qualifications Regulations has meant that a wider group of providers, including those providing adult and community learning (ACL), have had to check that teaching staff are appropriately qualified. However, will this requirement help to ensure that there is ‘better’ quality provision or will it just be an additional cost that takes resources away from delivery of learning?